Teaching french at language center of Federal University of Espírito Santo during the COVID-19 pandemic - Paixão, Grace Alves da; Porsette, Igor Castilho (Universidade Estadual Paulista, 2021)
We report the experience of teaching French as a Foreign Language in the Language Center of the Federal University of Espírito Santo (NL-UFES) in the first academic semester of 2020, in the context of the pandemic by Covid-19. The focus of this study is to register a specific reality and, from this context, discuss topics related to learning French. The research was based on documents such as minutes of meetings, institutional ordinances, investigations carried out by the NL-UFES with students and data on enrollments and evasion. For our reflection about this subject, in this paper, we used theoretical contributions from de Magnoni and Silva (2014), Galli (2012), Kaspary (2012), Bianchini (2003) and Nitzke (1999). The conclusions point to the difficulties of the students remaining in the courses in the face of the new context, to the methodological adaptations necessary in the transition from classroom to virtual and to the non-traditional forms of assessment that the new reality makes emerge.